Strategi Guru Dalam Membimbing Belajar Siswa Broken Home di SDN 07 Kubang Putih: Strategi Guru dalam Membimbing Belajar Siswa Broken home DI SD N 07 Kubang Putiah - aziizirrahman, abdul; Trisno, Bambang (Indonesian Research Journal on Education, 2023)
This study aims to find out how the condition of children from broken-home families is broken home. To determine the impact of the Broken Home family on student learning activities. To find out the teacher's strategy in guiding the learning of broken home students at SD N 07 Kubang Putiah Agam, West Sumatra. Type. This research is a type of qualitative research. Data collection methods used are observation and interviews. The subjects of this study were students of class VI from the Broken Home family background. Broken Home in this study focuses on children who experience problems in learning activities at school due to their parent's divorce. The results showed that the learning activities of thesestudents had increased due to special guidance from the teacher at the school.